Study of the growth of common carp Cyprinus carpio in muddy ponds using a local diet - Dr. Kamil Kadhim Fahad; Zahraa Saeed Jabbar (University of Thi-Qar Journal of agricultural research, 2022)
The current study examined the culture of the common carp Cyprinus carpio in three lakes supplied with water from Shatt Al-Badaa, a section of the Euphrates River, located in the Al-Rifai district, the village of Al-Nazim, between latitude 46.0703 in the south and a length of 31.5540N. 2021 and up to (23/2/2022) Three standardized treatments were used in the culture density of 1000 fish/m3 divided into three lakes equally and with an average weight of 20 ± g. A standardized local diet was used to feed the fish. The temperature during the experiment ranged between 14-28 (C) values. pH (7-8.5), dissolved oxygen concentration (6.7-9.0) mg/L. Salinity ranged between 0.2-0.3) g/liter. The results of the statistical analysis of the protein efficiency ratio outperformed the fish of the third treatment (62.210). The results of the statistical analysis indicated that the percentage of protein in the muscles of fish after the experiment was higher, reaching 5.76%, while the lowest percentage in the muscles of fish before the experiment was 3.61. The percentage of protein decreased at the beginning of the experiment. We notice an increase in the percentage of protein deposited in the fish body at the end of the experiment. The results of the experiment when analyzed on the basis of dry weight showed a difference in the percentage of fat in the chemical analysis of fish muscles before the experiment, 0.0048%, while the percentage of fat in the chemical analysis of fish muscles after the experiment was 39%. This may be due to the large size of the fish during the experiment period, in addition to its adoption in Feeding on the natural food found in the ponds. The current study showed an increase in the percentage of ash in fish muscles before the experiment on the basis of dry weight, which amounted to 5.49 %, and we note a decrease in the percentage of ash in fish muscles before the experiment, on the basis of dry weight, of 4.25%. The results of the study showed that carbohydrates increased at the end of the experiment (from 0.00069 to 0.485). The results of our current study showed that the survival rate of fish was not affected by the survival rate in the months of the beginning of the experiment, October and November, except in the last months, December, January and February